Modeling Conic Section Using Hawgent Dynamic Mathematics Software - Ning Yiting; Jianlan Tang; Rafiantika M. Prihandini; Usman Aripin (ARITHMETIC: Academic Journal of Math, 2022)
Teachers should pay attention to the deep integration of information technology and mathematics courses, so as to achieve the effect that traditional teaching methods are difficult to achieve. Conic section in high school is an important carrier for cultivating students' mathematical literacy, but it is highly abstract and comprehensive, making it a "difficult point" in high school mathematics teaching. Hawgent dynamic mathematics software has powerful dynamic and visual functions, which can effectively assist the teaching of ellipse in high school. The questions to be studied in this paper are: (1) describe how teachers use Hawgent dynamic mathematics software to design learning media when teaching the content of conic section and stimulate students' for knowledge; (2) describe how Hawgent dynamic math software be used in class to help students understand the definition of conic section effectively. This research was used the research method combining ADDIE model and teaching experiment to analyze the class using Hawgent dynamic mathematics software to design learning materials and the class using traditional teaching method. Research sample was 130 high school students. Mathematical software design learning materials, can give students an intuitive presentation of the formation process of the conic, so as to help students effectively understand mathematical concepts and stimulate students' curiosity for knowledge.